Tjommie en Vriende - an interactive language journey through the wonders of Afrikaans : a computer-based programme for international students. - Coetzee, Marisca (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Afrikaans and Dutch))—University of Stellenbosch, 2006.